The Role Of Auditor Individual Morality In Moderating The Relationship Of Love Of Money And Machiavellian Character Towards Accounting Fraud Tendency - Halik, Maria Yessica; Halik, Johannes Babtista; Sumanti, Dian Adhesive Fourtuniette; Mangampa, Stella Nirmala Meylani (E-Jurnal Akuntansi, 2024)
The survey results (the Association of Certified Fraud Examiners (ACFE), 2020) in 2022 showed 2,448 fraud cases reported by 125 countries in the world based on eight focus areas. Grouping of country cases in the Asia Pacific region, Indonesia ranks first with the most fraud cases totaling 36 cases followed by China 33 cases, Australia 29 and the Philippines 24. This study aims to analyze the influence of the love of money and its Machiavellian nature on the tendency of accounting fraud with individual morality as a moderating variable. This study was conducted at a Public Accounting Firm (KAP) in Makassar City with 65 auditors as respondents. Data were analyzed using Partial Least Square (PLS). The results of the study indicate that love of money and Machiavellian nature have a significant effect on the tendency of accounting fraud. Other research results show that individual morality can moderate the influence of the love of money and machiavellian nature on the tendency of accounting fraud. This indicates that a high love of money and a manipulative nature are the causes of auditors committing fraud. Still, auditor morality can be a deterrent factor for committing accounting fraud.